Intracranial Rosai Dorfman Disease: report of three cases and literature review - Symss, Nigel Peter (Medknow Publications Pvt Ltd, 2010)
BACKGROUND: Rosai-Dorfman Disease (RDD) is a rare idiopathic non-neoplastic histioproliferative disease characterized clinically by massive painless cervical lymphadenopathy, fever and weight loss. Extranodal involvement has also been recognized. Central nervous system (CNS) manifestations are extremely rare and patients with intracranial involvement usually present with clinical and radiological findings suggestive of a meningioma. CASE DESCRIPTION: We report our experience in the management of three patients with RDD. Two patients had dural based lesions, radiologically in favour of a meningioma, and one patient had a parenchymal lesion suggestive of a tuberculous granuloma. Treatment consisted of total excision in one case, and subtotal excision followed by conventional radiotherapy in two cases. The diagnosis was confirmed by histopathology and immunochemistry which is essential for a definite diagnosis of RDD.